SENTIMENT ANALYSIS ON STUDENTS’ PERSPECTIVE TOWARD ENGLISH ONLINE LEARNING USING WORD FREQUENCY ANALYSIS - Simatupang, Ervina CM; Zuraida, Ida; Illana, Mary Ann A.; Rodelas, Allan Nicko (University of Kuningan, 2024)
The post-pandemic situation has triggered a seismic shift in the education landscape, forcing educational institutions worldwide to transition to online learning platforms. Understanding students' perspectives towards this abrupt transformation is crucial for improving the quality of online education. This study employs sentiment analysis techniques, specifically Word Frequency Analysis, to gain insights into students' sentiments and opinions concerning online learning. Using a dataset of student responses collected through surveys and open-ended questions, the researchers conducted a comprehensive analysis of the words and phrases frequently used by students when describing their experiences with online learning. Through the systematic identification of prominent words and their frequencies, this research provides a valuable overview of the prevailing sentiments, concerns, and areas of satisfaction among students. The findings reveal a nuanced picture of students' attitudes. While positive sentiments such as “nyaman”, “baik”, and “responsif